Polymerase Synthesis of Hypermodified DNA Displaying a Combination of Thiol, Hydroxyl, Carboxylate, and Imidazole Functional Groups in the Major Groove - Kaiser, Lukáš; Ondruš, Marek; Poštová Slavětínská, Lenka; Raindlová, Veronika; Hocek, Michal (Chemistry (Weinheim an der Bergstrasse, Germany), 2025)
We designed and synthesized a set of six 2'-deoxyribonucleoside 5'-O-triphosphates (dNTPs) bearing functional groups mimicking amino acid side chains in enzyme active sites (OH, SH, COOH, and imidazole) attached to position 5 of pyrimidines or position 7 of 7-deazapurines through different linkers. These modified dNTPs were studied as substrates in enzymatic synthesis of modified and hypermodified DNA using several DNA polymerases. In primer extension (PEX), all modified dNTPs provided DNA containing one, two, three, or, (all) four modified nucleotides each bearing a different modification, although the thiol-modified dNTPs were worse substrates compared to the others. In PCR, we observed exponential amplification for any combination of one, two, or three nonsulfur dNTPs but the thiol-modified dNTP did not work well in any combinations. Sequencing of the hypermodified DNA confirmed the good fidelity of the incorporation of all the modified nucleotides. This set of modified dNTPs extends the portfolio of building blocks for prospective use in selections of functional nucleic acids.
Keywords: polymerázová řetězová reakce; kyseliny karboxylové; puriny; Polymerase Chain Reaction; nucleotides; DNA-dependentní DNA-polymerasy; polymerases; Purines; enzymatic syntheses; DNA-Directed DNA Polymerase; Carboxylic Acids; katalytická doména; Sulfhydryl Compounds; DNA; Imidazoles; Catalytic Domain; imidazoly; sulfhydrylové sloučeniny